PERKEMBANGAN PENDIDIKAN ISLAM MASA AWAL DI JAWA, LEMBAGA & TOKOHNYA - Rubi Awalia; Bahaking Rama; Muhammad Rusydi Rasyid (CV. ADIBA AISHA AMIRA, 2023)
The discovery of Fatimah bint Maemun's tomb in Leran, Gresik, East Java, which dates to 1082 AD, signaled the entrance of Islam in Java. Additionally, the contribution of historical characters or scholars known as Wali Songo, which included Sunan Gresik, Sunan Ampel, Sunan Giri, Sunan Bonang, Sunan Kalijaga, Sunan Gunung Jati, Sunan Drajat, Sunan Kudus, and Sunan Muria, could not be separated from the entrance of Islam in Java. By using tactful and nonviolent preaching techniques, namely a cultural approach using art media, including wayang, gamelan, Javanese music, and traditional rites coupled with Islamic teachings, so that Islam is not perceived as a threat to other religions. The dispersion was also utilized in addition. Additionally, the dissemination was done through educational channels by building Islamic boarding schools where those who helped promote Islam in Java and its surroundings could assemble and study. The development of Islamic kingdoms in Java, such as the Demak Kingdom, the Cirebon Kingdom, the Banten Kingdom, and the Pajang Kingdom, also contributed to the growth of Islam in Java.